Phytochemical properties, yield and yield attributes of promising country bean genotypes grown in acidic soil condition during winter - Nath, D D; Islam, M S; Debnath, B (Journal of the Sylhet Agricultural University, 2025)
An experiment with three promising country bean genotypes- BARI Sheem-1, Sikribi Sheem-1 and Goalgadda was conducted at the experimental field and laboratory of Horticulture Department, Sylhet Agricultural University, from November 2022 to March 2023. The objective was to observe their growth, green pod and seed yield, nutrition and phytochemical properties in acidic soil condition of Sylhet. The RCB (Randomized Complete Block) design was used with three replications. Days to first flower was found earlier for Sikribi Sheem-1 (48.50 days) and BARI Sheem-1 (51.75 days). Sikribi Sheem-1 recorded the earliest harvest at 71.5 days. The highest number of green pods plant-1 was in Sikribi Sheem-1 (582.5), while Goalgadda had the lowest (329.45). Goalgadda also had the largest fruit size with pod length (13.95 cm) and breadth (3.37 cm), leading to the heaviest individual fruit weight (10.14 g). Despite having the fewest pods, Goalgadda matched the pod yield of the other varieties due to its heavier fruit. Sikribi Sheem-1 had the highest number of dried pods (477.75), seed yield plant-1 (347.50 g), and seed yield ha-1 (2.37 ton). Goalgadda had the heaviest 100-seed weight (50.52 g). In green pods, Goalgadda had the lowest fibre (0.25%) and crude fibre (6.30%), indicating it is more palatable. Goalgadda also had the highest ash content (6.73%), while Sikribi Sheem-1 had the highest crude protein (26.51%) and BARI Sheem-1 had the most Vitamin C (13.21 g100g-1). Goalgadda exhibited the highest phytochemical properties with total phenolic content (14.60 μgmg-1) and antioxidant activity (31.12%). The flavonoid content was significantly higher in BARI Sheem-1 (3.36 μgmg-1) and Goalgadda (3.11 μgmg-1) compared to Sikribi Sheem-1 (2.22 μgmg-1). All three varieties are nutrient-rich and suitable for cultivation in acidic soils for pod production, with Sikribi Sheem-1 being the best for seed production. J. Sylhet Agril. Univ. 11(1): 67-74, 2024